Fluorine‐Free Noble Salt Anion for High‐Performance All‐Solid‐State Lithium–Sulfur Batteries. Issue 25 (27th May 2019) - Zhang, Heng; Judez, Xabier; Santiago, Alexander; Martinez‐Ibañez, Maria; Muñoz‐Márquez, Miguel Ángel; Carrasco, Javier; Li, Chunmei; Eshetu, Gebrekidan Gebresilassie; Armand, Michel
Abstract: Amongst post‐Li‐ion battery technologies, lithium–sulfur (Li–S) batteries have captured an immense interest as one of the most appealing devices from both the industrial and academia sectors. The replacement of conventional liquid electrolytes with solid polymer electrolytes (SPEs) enables not only a safer use of Li metal (Li°) anodes but also a flexible design in the shape of Li–S batteries. However, the practical implementation of SPEs‐based all‐solid‐state Li–S batteries (ASSLSBs) is largely hindered by the shuttling effect of the polysulfide intermediates and the formation of dendritic Li° during the battery operation. Herein, a fluorine‐free noble salt anion, tricyanomethanide [C(CN)3 −, TCM − ], is proposed as a Li‐ion conducting salt for ASSLSBs. Compared to the widely used perfluorinated anions e.g., bis(trifluoromethanesulfonyl)imide anion, [N(SO2 CF3 )2 )] −, TFSI − , the LiTCM‐based electrolytes show decent ionic conductivity, good thermal stability, and sufficient anodic stability suiting the cell chemistry of ASSLSBs. In particular, the fluorine‐free solid electrolyte interphase layer originating from the decomposition of LiTCM exhibits a good mechanical integrity and Li‐ion conductivity, which allows the LiTCM‐based Li–S cells to be cycled with good rate capability and Coulombic efficiency. The LiTCM‐based electrolytes are believed to be the most promising candidates for building cost‐effective and high energy density ASSLSBs in the near future. Abstract : Fluorine‐free noble salt anion, tricyanomethanide [C(CN)3 −, TCM − ], is proposed as a Li‐ion conducting salt for all‐solid‐state Li–S batteries (ASSLSBs). The superior chemical and electrochemical properties of TCM − salt endow ASSLSBs with good cycling stability and rate capability. The TCM − salt emerges as a promising candidate for building cost‐effective, environmentally benign, and high energy density batteries.